Introduction to mathematical modeling and chaotic dynamics - Upadhyay, Ranjit Kumar; Iyengar, S. R. K. (Satteluri R. K.) 1941- (CRC Press, 2014)
"Focusing on applications rather than theory, this book elucidates the real-life utilization of mathematical modeling and modern mathematical methods, such as bifurcation analysis, dynamical system theory, nonlinear dynamics, and chaotic dynamics. It provides a practical understanding of how the models are used in current research in the areas of population dynamics, physical science, and engineering, and contains a large number of solved examples, applications, and hints to unsolved problems. The text covers all fundamental concepts and mathematical skills needed to build models and do analyses and also provides an informative overview of known literature"-- Provided by publisher.